2016
DOI: 10.1002/cctc.201501119
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hydrogen Evolution Catalysis Based on Cu Nanoparticles Deposited on Carbon Nanotubes at the Liquid/Liquid Interface

Abstract: Copper nanoparticles were electrodeposited in situ on a conductive multi‐walled carbon nanotubes (MWCNT) support at a free‐standing water/1,2‐dichloroethane interface. The Cu/MWCNT nanocomposites act as highly active hydrogen evolution catalysts at the interface in the presence of lipophilic decamethylferrocene as the reducing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…According to these results, the rates of the reaction were about 690 and 2000 times higher in the presence of the Ni x S y and Ni x S y /CNT catalysts, respectively, than if the reaction was performed in the absence of a catalyst. The reaction rate was also increased by a factor of 6 by using only the CNTs, and this increased rate might have originated from trace amounts of metal impurities in the commercially available CNTs , , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to these results, the rates of the reaction were about 690 and 2000 times higher in the presence of the Ni x S y and Ni x S y /CNT catalysts, respectively, than if the reaction was performed in the absence of a catalyst. The reaction rate was also increased by a factor of 6 by using only the CNTs, and this increased rate might have originated from trace amounts of metal impurities in the commercially available CNTs , , …”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that four‐electrode voltammetry performed at the interface of water and the organic phase was an effective method to study catalytic reactions . Thus, the catalytic activities of Ni x S y and the Ni x S y /CNT composite for the HER by DMFc were investigated by potentiostatic polarization of the water/DCE interface (Scheme b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(C), blue trace . Glassy carbon and platinum disc electrodes were used as the working and counter electrodes respectively, while the reference electrode was a Ag + /Ag DJ-ORE. Pt or Pd salts at the interface in the presence of an oil-based electron donor) 15,29 or, more simply, by floating pre-formed H 2 evolution catalytic nanoparticles 20,[30][31][32][33][34][35][36][37][38][39] or nanocomposites [40][41][42] at the water-organic interface (Scheme 5(C)). These floating catalysts can significantly improve efficiency in terms of turnover frequency of [Cp 2 *Fe (III) ] + consumption/regeneration cycles.…”
Section: Resultsmentioning
confidence: 99%
“…As the catalyst support, extensive efforts have been made in the past several decades. There are many applications of CNTs which are often hybridized by organic polymer [9], graphene oxide [10], metallic oxide [11,12], metal (Ni, Pt, Au) [13,14], along with other materials. These nanocomposites express special advantages in the high surface area to volume ratios, which provide a unique opportunity for catalyst supports, enhancing the catalyst longevity and sensitivity [15].…”
Section: Introductionmentioning
confidence: 99%